Droits de l'homme, droits de Dieu: Une inévitable tension ? - Ferrari, Silvio (Social compass, 2018)
The conflicts between rights of God and human rights are on the rise. On the one hand, there are some rights that are qualified as human rights in the most important international conventions and in many national constitutions. As such, they are to be respected always and everywhere. On the other hand, there are rights that are directly or indirectly attributed to the will of God. Their respect is regarded as a religious obligation to be upheld even when it implies the violation of human rights. These are the terms of the conflict and the fact that they sink their roots in non-negotiable beliefs - rights related to the very nature of man vs. rights dependent on the will of God-makes this conflict particularly serious and complex. This article discusses the structural and historical causes of this conflict and proposes a few strategies to reduce the tensions between these two sets of rights.